EKSISTENSI MAHKAMAH KEHORMATAN DEWAN PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 2 TAHUN 2018 TENTANG MAJELIS PERMUSYAWARATAN RAKYAT, DEWAN PERWAKILAN RAKYAT, DEWAN PERWAKILAN DAERAH, DAN DEWAN PERWAKILAN RAKYAT DAERAH - Wahyu (Paulus Law Journal, 2020)
The Court of Council Honorific is one of complementary council organ which has a purpose in establishing a code of conduct. This study aims to know and analyze the existence of Court of Council Honorific. The study uses a normative method. The result of the study shows based on Act 17 in 2014, and than Act 2 in 2018 explain that the Court of Council Honorific has constancy which membership belongs to the inside parliament. In the violation of a certain code of ethics, it allow for elements from outside of the Court of Council Honorific. That is to dismiss that notion the Court of Council Honorific is not independent to handle the council members who suspected of breaking the code of conduct.